689 IMPACT OF RENIN-ANGIOTENSIN SYSTEM INHIBITORS ON CLINICAL OUTCOME IN HYPERTENSIVE PATIENTS WITH SEVERE AORTIC STENOSIS UNDERGOING TRANSCATHETER AORTIC VALVE IMPLANTATION: INSIGHT FROM THE EFFECTAVI REGISTRY. (15th December 2022) - Basile, Christian; Mancusi, Costantino; Franzone, Anna; Avvedimento, Marisa; Angellotti, Domenico; Castiello, Domenico Simone; Mariani, Andrea; Manzo, Rachele; Cirillo, Plinio; De Simone, Giovanni; Esposito, Giovanni
Abstract: Aims: Left ventricular pressure overload is connected with cardiac renin–angiotensin system activation, which may lead to myocardial fibrosis and poorer clinical outcomes. Hypertensive patients with symptomatic, severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) in the EffecTAVI registry were evaluated for the association between baseline treatment with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) and clinical outcomes. Methods and results: The research comprised 373 patients with moderate, high, or prohibitive risk who had TAVI in the EffecTAVI registry (NCT05235555). Using Kaplan–Meier event rates and study-stratified multivariable Cox proportional hazards regression models, we evaluated clinical outcomes at 2 years according to ACEi/ARB therapy status at baseline. Among the 327 patients with hypertension included in the present study, 222 (67.9%) were treated with ACEI/ARB at baseline, whereas 105 (32.1%) were not. Treatment with ACEI/ARB was related with decreased all-cause mortality (HR=0.46, 95% CI 0.25-0.90, p=0.011), although this association was not statistically significant after multivariable adjustment for important covariates. Analyzing pre-procedural ACEi and ARBs separately, ARBs administration was related with a 58% decrease in all-cause mortality (HR=0.42, 95% CI 0.18-0.98, p=0.04), which was confirmed in multivariate analysis. Conclusion: In a small cohort of hypertensive patients with severe symptomatic AS from the EffecTAVI registry, ARBs treatment at baseline was independently associated with a lower risk of 2-year all-cause mortality.